A molecular-level superhydrophobic external surface to improve the stability of metal–organic frameworks. Issue 35 (23rd August 2017) - Sun, Yuxiu; Sun, Qi; Huang, Hongliang; Aguila, Briana; Niu, Zheng; Perman, Jason A.; Ma, Shengqian
Abstract : A facile and reliable molecular-level modification strategy was developed to impart superhydrophobicity to the external surface of porous metal–organic frameworks. The obtained Zr-based MOFs well inherit their original crystalline nature and remain stable under various conditions. Abstract : In this work, we demonstrate a facile molecular-level modification method that imparts superhydrophobic character to Zr-based MOFs, while retaining their high porosity. Alkyl phosphonic acids, such as n -octadecylphosphonic acid (OPA), interact with the zirconium oxide clusters situated near and on the surface of the MOF. The octadecyl alkyl chains reduce the surface free energy on the MOF's exterior, yielding a superhydrophobic material with a contact angle greater than 150°. After exposure to aqueous solutions with a high pH and high ionic strength, the OPA-MOFs retain nearly identical surface areas. Notably, the OPA-MOFs are capable of separating organic liquids from water, which could facilitate oil/water separation applications in the event of an oil spill.